2023
DOI: 10.1111/sltb.12945
|View full text |Cite
|
Sign up to set email alerts
|

Suicide among lawyers: Role of job problems

Abstract: Introduction Suicide research has neglected the legal profession. The present investigation determines what risk factors distinguish lawyers' suicides from those of the general population. Given the substantial investment in their careers, client dependency, and ongoing stress of work, job problems are seen as key potential drivers of lawyers' suicides. Methodology Data are from the National Violent Death Reporting System (NVDRS). They refer to 30,570 suicides. Fifteen predictors, including social strains, psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…In this study, a stable marital status was one of the protective factors for NSSI in female patients with mood disorders. Stable marital status provides patients with social, financial, and emotional support, and reduces their isolation by providing them with opportunities to interact ( 48 , 49 ); their spouses’ support in the monitoring of health-related behavior may also help encourage a healthy lifestyle ( 50 , 51 ). A study was also conducted in Beijing among patients with mood disorders, marital status was compared between patients with and without NSSI and found that being unmarried was a risk factor for NSSI in patients with depression and bipolar disorder ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a stable marital status was one of the protective factors for NSSI in female patients with mood disorders. Stable marital status provides patients with social, financial, and emotional support, and reduces their isolation by providing them with opportunities to interact ( 48 , 49 ); their spouses’ support in the monitoring of health-related behavior may also help encourage a healthy lifestyle ( 50 , 51 ). A study was also conducted in Beijing among patients with mood disorders, marital status was compared between patients with and without NSSI and found that being unmarried was a risk factor for NSSI in patients with depression and bipolar disorder ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…In many Western countries, being unmarried or divorced is often associated with a higher risk of suicidal behavior, while being married is generally considered protective. 4 , 70 However, studies in South Asia have shown a higher proportion of married individuals among those engaging in suicidal behavior. 59 , 68 , 71 , 72 , 73 This contrasting finding suggests that the association between marital status and suicidal behavior may be influenced by cultural, social, and economic factors specific to the South Asian region.…”
Section: Discussionmentioning
confidence: 99%
“…Among various psychosocial factors, marital status is linked with social and community integration, 4 and in turn, is associated with social isolation and its further consequences including suicidal behavior. 5 While marriage could enhance social integration and regulation leading to chances of reducing suicidal risk, divorce, on the other hand, could increase suicide risk by breaking the marriage and relationships between the individual.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also found 'social isolation' and 'violence' as two of the most common positive SBDH predictors. Prior studies showed a higher association between social isolation and suicide risk 12,[42][43][44][45] . Exposure to violence is also a well-known risk factor for suicidality 12,46,47 .…”
Section: Ensemble Learningmentioning
confidence: 92%